THE FLIPPED CLASSROOM BASED ON E-LEARNING IN ENGLISH COURSES - Marleen M.A.F.Q Sumampouw (KOMPETENSI, 2021)
Flipped classroom is a type of blended learning that is applied at various levels of education, from elementary to university, but there is still a lack of research on its use in English education. The aim of this article is to provide a brief overview of the impact and effectiveness of the flipped classroom on English learning. The research methodology used is a literature study with an analysis of several articles about the flipped classroom, which ends with the research objective. The results of the study show that the flipped classroom effect can increase students' active learning and independence, increase collaboration, and improve learning outcomes. This article provides advice for educators, especially in the field of English education, regarding the use of the flipped classroom in maximizing the learning carried out. The conclusion of the study, comparing the flipped classroom learning model in general shows that the flipped classroom learning model is effectively used in the learning process because students have studied the material before entering class, meaning that the lecturer no longer dominates the classroom situation and the interaction between lecturers and students becomes better and more enjoyable